Evaluación de tres niveles de pollinaza en la etapa de crecimiento -engorde de cuyes en el cantón Chaguarpamba, provincia de Loja - Reyes Encalada, María Elena (2014)
This work was carried out in the canton Chaguarpamba of Loja province, with the purpose of generating alternatives for improving the nutrition of the guinea pigs, through the use of manure, as supplementary ration that permit to ensure the supply of nutrients necessary and increase production levels. They were 80 guinea pigs (40 females and 40 males) from one month of age with an average weight of 200g. Previous to the development of the ration, the treatment of manure was performed by exposure to sunlight, they were used to eliminate odors and pathogens, then, it was proceeded to grind and sift in order to supply according to the respective treatments. The experiment was directed as a 2 x 4 factorial arrangement (sexes manure levels), resulting in eight treatments, which were arranged in a randomized block design, considering each week as a block or repetition. The following variables were studied: forage intake, consumption of poultry manure, weight gain, feed conversion, mortality and profitability. The results show that the higher feed intake, weight gain and feed conversion was obtained in the treatment eight (males 30% of manure), with 5872 g, 1254 g and 4.6 respectively, while mortality was 8,75 %, with the highest incidence in the treatment five (30 %), while the higher profitability was generated in the treatment seven (males 20% of manure) with 27.5%. It concludes that the manure is a good alternative to supplement the diet of guinea pigs in the province of Loja.